Perancangan Filter Frame Instagram Untuk Hari Tata Ruang Nasional 2023 PT. Urban Spasial Indonesia Menggunakan Software Spark AR - Clara Oktavia Firdaus; Alfian Candra Ayuswantana (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In commemorating National Spatial Planning Day 2023, PT Urban Spatial Indonesia has crafted an Instagram filter using Spark AR software. This filter serves as a creative and interactive media and functions as an educational tool. Using a qualitative case study method, this research is organized by defining the concept and design of the filter. The evaluation indicates a positive response with a significant number of user engagements. It is hoped that the design of this filter can contribute to enhancing public awareness and appreciation for the importance of spatial planning.